Custom-made macroporous bioceramic implants based on triply-periodic minimal surfaces for bone defects in load-bearing sites. (June 2020) - Charbonnier, Baptiste; Manassero, Mathieu; Bourguignon, Marianne; Decambron, Adeline; El-Hafci, Hanane; Morin, Claire; Leon, Diego; Bensidoum, Morad; Corsia, Simon; Petite, Hervé; Marchat, David; Potier, Esther
Abstract: The architectural features of synthetic bone grafts are key parameters for regulating cell functions and tissue formation for the successful repair of bone defects. In this regard, macroporous structures based on triply-periodic minimal surfaces (TPMS) are considered to have untapped potential. In the present study, custom-made implants based on a gyroid structure, with (GPRC) and without (GP) a cortical-like reinforcement, were specifically designed to fit an intended bone defect in rat femurs. Sintered hydroxyapatite implants were produced using a dedicated additive manufacturing technology and their morphological, physico-chemical and mechanical features were characterized. The implants' integrity and ability to support bone ingrowth were assessed after 4, 6 and 8 weeks of implantation in a 3-mm-long, femoral defect in Lewis rats. GP and GPRC implants were manufactured with comparable macro- to nano-architectures. Cortical-like reinforcement significantly improved implant effective stiffness and resistance to fracture after implantation. This cortical-like reinforcement also concentrated new bone formation in the core of the GPRC implants, without affecting newly formed bone quantity or maturity. This study showed, for the first time, that custom-made TPMS-based bioceramic implants could be produced and successfully implanted in load-bearing sites. Adding a cortical-like reinforcement (GPRC implants) was a relevant solution to improve implant mechanical resistance, and changed osteogenic mechanism compared to the GP implants. Statement of significance: Architectural features are known to be key parameters for successful bone repair using synthetic bioceramic bone graft. So far, conventional manufacturing techniques, lacking reproducibility and complete control of the implant macro-architecture, impeded the exploration of complex architectures, such as triply periodic minimal surfaces (TPMS), which are foreseen to have an unrivaled potential for bone repair. Using a new additive manufacturing process, macroporous TPMS-based bioceramics implants were produced in calcium phosphate, characterized and implanted in a femoral defect in rats. The results showed, for the first time, that such macroporous implants can be successfully implanted in anatomical load-bearing sites when a cortical-like outer shell is added. This outer shell also concentrated new bone formation in the implant center, without affecting new bone quantity or maturity. Graphical abstract: Image, graphical abstract